Modeling the Intricate Association between Sustainable Service Quality and Supply Chain Performance with mediating role of Blockchain Technology in America. - ABISOLUWA ABRAHAM ODUTOLA (International Journal of Multidisciplinary Research and Studies, 2021)
Industries are increasingly becoming conscious of the limitation of natural resources, prompting businesses to adopt sustainability measures. The manufacturing/service sectors, which encompasses small and medium-sized enterprises engaged in logistical operations, actively implements strategies to attain the anticipated sustainability objectives. Integrating sustainable service quality qualities has recently become vital for achieving competitive advantages and sustainability goals. The present study investigates the impact of sustainable service quality attributes on sustainable supply chain performance (SSCP) and the attainment of triple-bottom-line sustainability outcomes. Using random sampling, the data was collected from 312 small and medium-sized logistics service providers in America. The collected data were subsequently analyzed using the Statistical Package for the Social Sciences (SPSS). Based on the results, there is a positive correlation between SSQAs and SSCP. Blockchain technology (BT) is crucial in mediating the relationship between SSQAs and SSCP. Additionally, BT is substantially influential mediating in the relationship between SSQAs and SSCP. This study contributes to the existing knowledge in the field of sustainability by examining the distinct relationship between sustainable service quality features and SSCP. The study presents novel findings on the subject issue within the context of 312 logistics small and medium-sized enterprises (SMEs) in a country such as the United States of America. The study's results are valuable for managers seeking to enhance their services by integrating SSQAs and cultivating their teams with the requisite knowledge and resources to attain desired goals.